Ambiguities in results obtained with 2D gel replicon mapping techniques. - Linskens, M H (1990)
Recently, two 2-dimensional (2D) gel techniques, termed neutral/neutral and neutral/alkaline, have been developed and employed to map replication origins in eukaryotic plasmids and chromosomal DNA (1-11). The neutral/neutral technique, which requires less DNA for analysis, has been preferentially used in recent studies. We show here that the signal predicted for an origin is not detected using the neutral/neutral technique if the origin is located near the end of the analyzed restriction fragment. We also demonstrate that analysis of the same batch of DNA by the two different mapping techniques can generate apparently contradictory results: in some situations where neutral/alkaline 2D analysis indicates that a certain origin is always used, neutral/neutral 2D analysis suggests that the origin is not always used. Several possible explanations for this type of disagreement between the two techniques are discussed, and we conclude that it is important to use both techniques in combination in order to minimize possible misinterpretations.